(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the pedagogical, psychological, and social aspects of involving children with special needs in inclusive education. It analyzes the theoretical foundations of inclusive education, the problems encountered in practice, and the ways to overcome them. The paper also presents recommendations aimed at expanding the opportunities for children with special needs to study in general educational institutions.